Decifrare il Madrigale di Leopardi (ENTHYMEMA, 2022)
This article focuses on Leopardi’s Madrigale, which was left unpublished by the author, and found on a single manuscript page among the so-called Neapolitan papers. It appears in two versions, with three variant lines at the bottom of the page. Philologists reasonably consider the second version to be nearer to the author’s will. It is, however, unclear what exactly distinguishes it from the first one. Here, I argue that specific poetic structures set the two versions apart (namely, prosodic phrasing, the metrical structure of one variant line, and the distribution of personal pronouns in the text). After proposing an analysis of these three types of structures, I critically discuss some of the most relevant questions arising from the structural approach. On this basis, I provide a reading of the above analysis drawing on both sociological aesthetics and anthropology, in order to decipher the nature of the Madrigale as a ‘negative Dinggedicht.’
Keywords: Leopardi; Madrigale; Structuralism; Prosodic Phrasing; Binary Structure; Object–Gift